Karl Marx y el campo pedagógico Ensayos a partir del estudio colectivo de sus textos tempranos (1839-1848) - Olivares, Cristián; Cabaluz, Fabián; Zurita, Felipe (Ariadna Ediciones, 2023)
The book you have in your hands is the result of a process of collective construction, openly positioned within the broad Marxist field. Its content refers to a set of eleven essays created from the enriching experience of what was the Study Circle "Early Writings of Karl Marx (1839-1848). Collective reading from the educational and pedagogical field", developed in Santiago de Chile during the year 2020, which was organized by the Center for the Study of Marxisms and Education (CEMED), which is the name that preceded our current Study Group in "Popular Education and Emancipatory Pedagogies" (GEPEM). We are interested in emphasizing our invitation to educators of Our America to read Marx with their feet in the neighborhood, the population, the towns, the favelas, the unions, the organizations, the political parties and the movements, hand in hand with our community, territorial, political, pedagogical, militant and union work.